High hopes [videorecording (DVD)] - Leigh, Mike, 1943-; Davis, Philip, 1953-; Sheen, Ruth; Tobias, Heather; Doré, Edna, 1921-2014 (Indie feature collection., 2009)
Cyril and Shirley are a young, working-class couple who, in their struggle to make ends meet, have become absorbed in socialism. Cyril's sister Valerie and her husband aspire to a more privileged class. The only glue holding the siblings together is their withdrawn and wistful old mother.